Information System Design Planning And Control Of Aluminum Raw Material Inventory Case Study At PT Mamagreen Pacific - Maysaroh; Saputra, Deni (ADPEBI, 2022)
PT Mamagreen Pacific has been running for approximately nineteen years. For a long period in data processing, it still uses a manual system to input data for incoming and outgoing goods and requires a long time to manage. Therefore it is necessary to find alternatives to handling the problem. When viewed from the current era of globalization, the use of computers is expected to solve existing problems, not only calculations but also the ability to store data and convey information quickly and accurately that can be accessed in real-time. The system that will be applied to the PPIC division, especially for the aluminum raw material warehouse section, follows the stages of system development using the prototype, which consists of four main steps: requirements collection, planning, design, and implementation. An evaluation prototype for the system is already made. Evaluation prototype that has been carried out using usability testing, the results show that the five aspects starting from the elements of learnability, efficiency, memorability, errors, and satisfaction have an average value above 3, indicating that the Stock RM Aluminum has taken into account the usability or is already usable. This application program is made to find the stock of aluminum raw materials still available in the warehouse. This application program is designed using the MySQL program as a database for data storage, while the programming language uses PHP to design the program interface